Контроль реологічних властивостей матеріалів у системах керування енергоощадними технологічними процесами - Крих, Г. (Видавництво Національного університету “Львівська політехніка”, 2004)
The application of hydrodynamic devices for a measurement of rheological parameters of food materials in automatic control systems by technological processes is justified with the purpose of an increase of energy consumption on their realization.
Keywords: 532.137; 681.2